The Effects of Employment Protection on the Choice of Risky Projects - Amihai Glazer; Vesa Kanniainen (Center for Economic Studies and ifo Institute (CESifo), 2002)
We consider a firm that is subject to employment protection laws that limit the firms ability to fire labor. In particular, we suppose that though a firm which shuts down can fire all its workers, it may fire no fewer. Compared to a firm that is subject to no employment protection, a firm constrained in firing will prefer a risk-free project over a risky one, but may prefer the riskier of two risky projects.
Keywords: 330; project choice; labor protection